2023
DOI: 10.3389/fcvm.2023.1052471
|View full text |Cite
|
Sign up to set email alerts
|

Chronic vagus nerve stimulation in patients with heart failure: challenge or failed translation?

Abstract: Autonomic imbalance between the sympathetic and parasympathetic nervous systems contributes to the progression of chronic heart failure (HF). Preclinical studies have demonstrated that various neuromodulation strategies may exert beneficial cardioprotective effects in preclinical models of HF. Based on these encouraging experimental data, vagus nerve stimulation (VNS) has been assessed in patients with HF with a reduced ejection fraction. Nevertheless, the main trials conducted thus far have yielded conflictin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…Regarding the frequency of stimulation, low frequencies (5–10 Hz) activate vagal afferents, whereas high frequencies (10–30 Hz) activate both vagal afferents and efferents (Castoro et al 2011 ). Accumulated data have shown that low-level VNS exacts paradoxical effects from high-level VNS (Wang et al 2019 ; Johnson et al 2018 ). Indeed, in addition to alleviating inflammation, high-level VNS reduced the lower heart rate and inhibited cardiac remodeling (Wu et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the frequency of stimulation, low frequencies (5–10 Hz) activate vagal afferents, whereas high frequencies (10–30 Hz) activate both vagal afferents and efferents (Castoro et al 2011 ). Accumulated data have shown that low-level VNS exacts paradoxical effects from high-level VNS (Wang et al 2019 ; Johnson et al 2018 ). Indeed, in addition to alleviating inflammation, high-level VNS reduced the lower heart rate and inhibited cardiac remodeling (Wu et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that VNS has more short-term effects in male rats than in female rats (Yaghouby et al 2020 ; Yokota et al 2022 ). Meanwhile, apart from electrode design and stimulated-side selection, the “dose” of electrical therapies, including current intensity, frequency and duty cycle, could affect the therapeutic effect of VNS on infarcted heart (De Ferrari et al 2014 ; Jiao et al 2016 ; Kong et al 2012 ; Libbus et al 2017 ; Nishizaki et al 2016 ; Rousselet et al 2014 ; Soltani et al 2023 ; Wang et al 2019 ; Wu et al 2023 ; Yu et al 2016 ). The present study mainly focused on the effects of VNS on the metabolic patterns of VSMCs and angiogenesis after MI.…”
Section: Discussionmentioning
confidence: 99%
“…In the heart, cardiac ganglionated plexi (GPs) reside in fat pads, constituting the “intrinsic cardiac nervous system” ( 38 ). The neural regulation of the heart involves the coordinated interplay of the sympathetic and vagus nervous systems ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%